Mass Balance Reconciliation for Bilinear Systems: A Case Study of a Raw Mill Separator in a Typical Moroccan Cement Plant - Fellaou, S.; Bounahmidi, T. (Engineering, Technology & Applied Science Research, 2016)
Stream flow rates and their several compositions are measured in a typical cement raw mill separator. In order to simultaneously reconcile flow and composition measurements in this circuit, the component mass balances was included as constraints which contain the products of flow rate and composition variables in the data reconciliation problem. In this paper, the effectiveness of simultaneous procedures for bilinear data reconciliation is established, the numerical problem constraints were coded in MATLAB and a mass balance model is built. Moreover, based on the difference between the measured and reconciled data it was found that it performs optimally.